Home and outpatient electrostimulation in the treatment of urinary incontinence in women: a systematic review - Suele Moura Oliveira Coelho Caetano; Elma Gomes Pereira; Aline Moreira Ribeiro; Júlia Barros Brito; Clarcson Plácido Conceição dos Santos (BMC Women's Health)
Abstract Introduction and hypothesis Urinary incontinence (UI) is defined as any involuntary loss of urine and can be associated with urgency and/or physical exertion. Electrical stimulation (ES) has recently been identified as a proven therapeutic alternative for UI, with few side effects and low cost. This systematic review, registered on the Prospective Register of Systematic Reviews (RD42024528812), investigated whether home-based ES would be as viable as outpatient ES in the treatment of women with UI. Methods Study selection was conducted by two independent researchers across the following databases: Cochrane Central Register of Controlled Trials (CENTRAL), PubMed, Embase, Web of Science, Scopus, and PEDro (search conducted on February 25, 2024). We also searched the reference lists of eligible articles. There were no restrictions on date and language. The RoB2 and GRADE tools were used to assess methodological quality and evidence recommendation. Results 723 articles were found, and four trials were eligible. Very low-quality evidence indicated statistically significant differences in cure rates or improvement of urinary symptoms in women treated with both outpatient and home-based ES. Low-quality evidence recommends home-based ES in maintaining improvement of urinary symptoms, and moderate-quality evidence indicates no severity of symptoms in the home-based group. Conclusion Home-based ES is shown to be as effective as outpatient ES in the treatment of UI in women. However, data analysis revealed low-quality evidence regarding the cure or improvement of the women’s conditions.